Functionalization of N-arylglycine esters: electrocatalytic access to C–C bonds mediated by n-Bu4NI - Luo, Mi-Hai; Jiang, Yang-Ye; Xu, Kun; Liu, Yong-Guo; Sun, Bao-Guo; Zeng, Cheng-Chu (Beilstein Journal of Organic Chemistry, 2018)
An efficient electrocatalytic functionalization of N-arylglycine esters is reported. The protocol proceeds in an undivided cell under constant current conditions employing the simple, cheap and readily available n-Bu4NI as the mediator. In addition, it is demonstrated that the mediated process is superior to the direct electrochemical functionalization.
Keywords: C–C formation; electrochemical oxidative functionalization; n-Bu4NI; redox catalyst